The Philosophy of David Hume - Smith, Norman Kemp. author. aut Link
XL, 568 p.
Keywords: Norman Kemp Smith's The Philosophy of David Hume has long been regarded as a classic study by scholars in the field - a ground-breaking book that has since been unsurpassed in its comprehensive coverage of the ideas and issues of Hume's Treatise. This reissue brings this currently out-of-print and highly sought-after classic up-to-date with a new introduction by Don Garrett. Garrett's new introduction sets the book in its contemporary context and makes the case for its continuing importance in the field of Hume scholarship.